Environmental (re)qualification of springs as an instrument of urban resilience: the case of the Lageado watershed, São Paulo/SP - Silva, Luciano Abbamonte da; Koury, Ana Paula (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – Deepen the understanding of the constitution, in terms of environmental characteristics, of the set of springs that make up the Ribeirão Lageado watershed. Methodology – Empirical case study, whose theoretical approach underpins the analysis of field visits and the systematization of data generated for each of the twenty springs. Originality/Relevance – The study allowed the collection of a series of evidence that demonstrates how the accelerated urbanization process of the outskirts of São Paulo is taking place, whose interventions, in their rapid advancement, seem to escape official records. Results – The twenty springs were named, based on prominent elements of the road layout, which were categorized according to the environmental requalification potential of each one, whether high, medium or low. Theoretical/Methodological Contributions – The study presents a relatively quick exercise, but one that manages to fill, in terms of a planned preliminary analysis, gaps and outdated information in official records. Social and Environmental Contributions – The study demonstrates, from an environmental perspective, that each sub-basin of the system can be understood, and qualified, as a minimum unit of urban planning.